Protecting Offshore Wind Turbines against Ship Impacts by Means of Adaptive Inflatable Structures - Cezary Graczykowski; Jan Holnicki-Szulc (Shock and Vibration)
Collisions with small service ships are serious danger for offshore wind turbines. Installing torus-shaped adaptive inflatable structure that surrounds a wind turbine tower at water level is one method of effective protection. Proposed pneumatic structure contains several separate air chambers equipped with devices for fast inflation and pressure release. The system can be adapted to various impact scenarios by adjusting the level of initial pressure in each chamber and by controlling the release of compressed air during collision. The paper presents finite element simulation of ship collision with wind turbine tower protected by pneumatic structure, conducted using ABAQUS software. Introduced methods of pressure adjustment are aimed at mitigating tower and ship response. The performed feasibility study proves that inflatable structure can effectively protect the wind turbine tower and the ship against serious damage.